Perfil de sensibilidad y resistencia bacteriana en pacientes con bacteriemia en el hospital teofilo davila, periodo 2018 - Maldonado Riofrio, Ximena Damaris (Machala : Universidad Técnica de Machala, 2019)
Intrahospital infections is a challenge faced by the medical community, which leads to increased nosocomial morbidity and mortality. The knowledge of the sensitivity profile and antimicrobial resistance will allow the adequate use of antibiotics and avoid empirical treatment.. Objectives: To determine the sensitivity and bacterial resistance profile in patients with bacteremia at the Teófilo Dávila hospital during the 2018 period; through a source of indirect information that serves as a basis for decision making. Materials and methods: An observational cross-sectional descriptive study was carried out, through the analysis of the database of 200 patients admitted to the hospitalization service with a request for blood culture, during the months of June and July of 2018. Results and Conclusions: In the present study of the 200 blood cultures obtained from the database, 12 positive blood cultures were detected, equivalent to a 6% percentage, and 188 negative blood cultures, equivalent to a percentage of 94%. The isolated microorganism was klebsiella pneumoniae, with a percentage of 33.3% of the patients, followed by Staphylococcus haemolyticus, 25% and in a lower percentage Staphylococcus aureus as well as Echerichia coli, 16.6%; Acinetobacter baumannii, 8.3% .It has also been shown to be more sensitive to amikacin and resistance to benzylpenicillin. In addition to the early detection of the causative organism, it is appropriate to know the sensitivity and bacterial resistance, to opt for the appropriate treatment, improve prognosis, and in this way prevent multidrug resistance.
Las infecciones intrahospitalarias es un desafío al que se enfrenta la comunidad médica, lo que conlleva al incremento de la morbilidad y mortalidad nosocomial.. El conocimiento del perfil sensibilidad y resistencia antimicrobiana, permitirá el uso adecuado de antibióticos, y evitar el tratamiento empírico. Objetivos: Determinar el perfil de sensibilidad y resistencia bacteriana en pacientes con bacteriemia del hospital Teófilo Dávila durante el periodo 2018; mediante fuente de información indirecta que sirvan de sustento en la toma de decisiones. Materiales y método: Se realizó un estudio descriptivo observacional de corte transversal, atravez del análisis de la base datos de 200 pacientes ingresados en el servicio de hospitalización con solicitud de hemocultivo, durante los meses de junio y julio del 2018. Resultados y Conclusiones: En el presente estudio de las 200 hemocultivos obtenidas de las base de datos, se detectaron 12 hemocultivos positivos, equivale a un porcentaje 6 %, y 188 hemocultivos negativos, equivale a un porcentaje de 94%. El microorganismo aislado fue la klebsiella pneumoniae, con un porcentaje 33.3 % de los pacientes, seguido de Staphylococcus haemolyticus, un 25 % y en menor porcentaje Staphylococcus aureus al igual Echerichia coli, un 16.6 %; Acinetobacter baumannii, un 8.3 %.También se ha demostrado mayor sensibilidad a la amikacina y resistencia a bencilpenicilina. Además de la temprana detección del microorganismo causal, es oportuno conocer la sensibilidad y resistencia bacteriana, para optar por el tratamiento adecuado, mejorar pronóstico, y de esta manera prevenir la multidrogoresistencia.
Keywords: BACTERIEMIA; SENSIBILIDAD BACTERIANA; RESISTENCIA BACTERIANA; HEMOCULTIVOS